2015
DOI: 10.1210/en.2014-1675
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Distribution of Glucagon-Like Peptide-1 Receptor mRNA, Protein and Binding in the Male Nonhuman Primate (Macaca mulatta) Brain

Abstract: Glucagon-like peptide-1 (GLP-1) is released from endocrine L-cells lining the gut in response to food ingestion. However, GLP-1 is also produced in the nucleus of the solitary tract, where it acts as an anorectic neurotransmitter and key regulator of many autonomic and neuroendocrine functions. The expression and projections of GLP-1-producing neurons is highly conserved between rodent and primate brain, although a few key differences have been identified. The GLP-1 receptor (GLP-1R) has been mapped in the rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
4
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 86 publications
12
125
4
7
Order By: Relevance
“…Electrophysiological recordings in acute slices from rat hippocampus demonstrated that application of GLP-1 and Ex4 increased the amplitude and frequency of postsynaptic inhibitory currents in hippocampal CA3 pyramidal neurons (49). Additionally, a new transgenic mouse model expressing Cre-recombinase under the promoter for GLP-1R (79) demonstrated that GLP-1Rs are functional in a subset of hippocampal pyramidal cells (11), in support of the in situ hybridization data from the rat (65) and nonhuman primate (35).…”
Section: Hippocampusmentioning
confidence: 61%
“…Electrophysiological recordings in acute slices from rat hippocampus demonstrated that application of GLP-1 and Ex4 increased the amplitude and frequency of postsynaptic inhibitory currents in hippocampal CA3 pyramidal neurons (49). Additionally, a new transgenic mouse model expressing Cre-recombinase under the promoter for GLP-1R (79) demonstrated that GLP-1Rs are functional in a subset of hippocampal pyramidal cells (11), in support of the in situ hybridization data from the rat (65) and nonhuman primate (35).…”
Section: Hippocampusmentioning
confidence: 61%
“…For example, GLP-1 receptors (GLP-1Rs) are located on vagal afferents that innervate the gut in close proximity to L-cells (Richards et al 2014), indicating a possible paracrine gut-brain axis for mediating its glycaemic effects. However, GLP-1Rs are also located on neurons innervating the portal vein (Vahl et al 2007), on β cells of the pancreas , and in the central 230:3 nervous system (Shimizu et al 1987, Heppner et al 2015, all possible targets for GLP-1 action (described in more detail below). Nonetheless, most studies demonstrate that vagal neural transmission is necessary for nutrientinduced gut feedback as anaesthetics, neurotoxins or vagotomy abolishes nutrient-induced reductions in food intake (Schwartz 2011), and in the case of lipid-induced CCK release, the lowering of hepatic glucose production (Wang et al 2008a).…”
Section: Gut Peptide Signalling In Regulating Glucose Metabolismmentioning
confidence: 99%
“…This is a very important aspect of central food evaluation, as the taste of palatable food can induce an immediate reward that can be a powerful drive for food consumption, therefore leading to an increase in energy intake. Interestingly, GLP1 receptors have not only been found in the CNS (Shugrue et al 1996, Heppner et al 2014, but also in the mammalian taste buds (Shin et al 2008), and GLP1 signalling was shown to mediate sweet taste perception (Shin et al 2008). Therefore, we hypothesise that GLP1 and GLP1RA treatment may affect the central processing and reward value of palatable food and that this may be an important mechanism by which GLP1 contributes to the central regulation of feeding in humans.…”
Section: Introductionmentioning
confidence: 96%